Evolution of seismicity at Kiruna Mine - Dineva, S; Boskovic, M (Deep Mining 2017: Proceedings of the Eighth International Conference on Deep and High Stress Mining, 2017)
Kiirunavaara (Kiruna) iron ore mine owned by LKAB (Sweden) is one of the largest underground mines. Mining started in 1898 as an open pit mine. In mid-1950, the mine started a transition to underground mining and passed to only underground mining in 1962. More substantial problems with seismicity started in 2007-2008 when the deepest mining level was 907 m (ca. 670 m below surface). By 2016, the mining production is at 1,022–1,079 m Level (ca. 785–845 m below surface). More than one billion tonnes of ore have been extracted since the beginning of mining. The average yearly production in recent years is 28 million tonnes. By 2016 the mine has the largest underground seismic system in the world with 204 operational geophones. The number of the sensors (geophones with natural frequencies of 4.5, 14, and a few of 30 Hz) changed with the increasing of production depth. The major stages with seismic system upgrades are: August 2008–June 2009 with 112 installed geophones, and July 2012–September 2013 with 95 installed geophones. During 2016–2017 it is planned to install some additional 45 geophones. The study was carried out to identify some trends in seismicity as the mining goes deeper and to find the correlation with some main controlling parameters – volume and depth of the production in order to obtain information for future seismic hazard and risk analysis. Custom made applications within mXrap were utilised to carry out the spatial variations of seismicity. The analysis showed substantial difference between the seismicity in the three studied blocks – 15/16, 28/30, and 33-37/34, with the weakest seismic activity in Block 15/16 (Mmax 1.6, maximum observed magnitude), followed by Block 28/30 (Mmax 2.2), and then largest seismicity in Block 33-37/34 (Mmax 2.2). The daily seismicity rate increased substantially through the years only for Block 33-37/34. The seismicity correlates strongly with the production depth. In general a straightforward correlation between the production volume and number of larger events (M > 0) was not found for the three studied blocks, assuming there are other factors affecting the seismicity, e.g. geological structures, areas with contrast in geomechanical properties, etc. The spatial variations of some seismic source parameters were traced for varying periods of time, depending on the major production stages (opening of new levels, full production, closing) for the three blocks. The distributions of the cumulative seismic energy showed a maximum around and below the production. The cumulative seismic moment and number of events in most cases showed a maximum around and above the production, indicating caving in these areas. The static stress drop shows the largest values around and below the production on the footwall side, corresponding also to the areas with increased stress. The energy index showed increased stresses in the same areas (EI > 1). This study is only the first overview of the seismicity in Kiruna Mine. For seismic hazard assessment and risk analysis further more detailed studies with smaller time intervals need to be carried out to obtain more precise correlations between the seismic parameters and the production volume and depth, and other possible factors affecting seismicity (geological structures, areas with contrast geomechanical properties, etc.).
Keywords: mining-induced seismicity